1983
DOI: 10.1056/nejm198307073090106
|View full text |Cite
|
Sign up to set email alerts
|

Leydig-Cell Function in Children after Direct Testicular Irradiation for Acute Lymphoblastic Leukemia

Abstract: To assess the effect of testicular irradiation on testicular endocrine function, we studied 12 boys with acute lymphoblastic leukemia who had been treated with direct testicular irradiation 10 months to 8 1/2 years earlier. Insufficient Leydig-cell function, manifested by a low response of plasma testosterone to chorionic gonadotropin or an increased basal level of plasma luteinizing hormone (or both), was observed in 10 patients, 7 of whom were pubertal. Two of these patients had a compensated testicular endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
3

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(33 citation statements)
references
References 16 publications
3
27
0
3
Order By: Relevance
“…Ten of12 boys showed evidence of Leydig cell dysfunction 10 months-8.5 years after testicular irradiation (24 Gy in 12 fractions over 18 days) for acute lymphoblastic leukemia, indicated by a low testosterone response to an acute bolus of human chorionic gonadotropin (hCG) or an increased basal plasma LH level, or both (37). Similar findings were reported by Leiper et al (38).…”
Section: Radiation and The Testissupporting
confidence: 78%
“…Ten of12 boys showed evidence of Leydig cell dysfunction 10 months-8.5 years after testicular irradiation (24 Gy in 12 fractions over 18 days) for acute lymphoblastic leukemia, indicated by a low testosterone response to an acute bolus of human chorionic gonadotropin (hCG) or an increased basal plasma LH level, or both (37). Similar findings were reported by Leiper et al (38).…”
Section: Radiation and The Testissupporting
confidence: 78%
“…The vulnerability of the Leydig cell to radiation damage is known to be age-dependent ) and a high incidence of severe Leydig cell damage has been observed after testicular irradiation in childhood when the irradiation dose exceeds 20 Gy (Brauner et al, 1983;Leiper et al, 1983;Shalet et al, 1985). Castillo et al (1990) demonstrated normal testosterone responses to hCG in prepubertal boys who received 12-15Gy to the testes in a fractionated schedule.…”
Section: Test18mentioning
confidence: 99%
“…However, this test is difficult to implement as it lasts for several days. Anyway, Brauner (1983) found good correlation between GnRH-test and HCG-test in males if performed in postpubertal period. Actually, our subjects were tested in postpubertal period.…”
Section: Classification Tree Analysismentioning
confidence: 74%
“…Two of these patients had testicular RT (1200 cGy in 4 fractions). Other authors did neither observe clinically significant impairment of LC after the testicular dose of this size (Brauner et al 1983, Castillo et al 1999 (Pennisi et al 1975). All our 16 patients with LC damage had damage of germinal epithelium as well.…”
Section: Leydig Cell Damagementioning
confidence: 83%
See 1 more Smart Citation